2022
DOI: 10.1007/s11666-021-01307-7
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Influence of Jet Fluctuations on Particles in Plasma Spraying

Abstract: Instabilities and fluctuations of the plasma jet in a thermal spray process can have a significant influence on the particle in-flight temperatures and velocities, affecting the properties of resulting plasma-sprayed coatings. Presented in this paper is a novel method for capturing the effects particles are exposed to in the plasma spraying process. High-speed camera images of a plasma jet generated by a cascaded three-cathode plasma generator (TriplexPro-210) were recorded for varying operating conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A large number of numerical modelings [22,[26][27][28][29] and experimental studies [30][31][32][33][34] have been performed to analyze the mechanisms of anode erosion, and propose the methods to inhibit the anode erosion. The modeling found that the arc usually attached on the anode surface in the diffusive or constricted forms.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of numerical modelings [22,[26][27][28][29] and experimental studies [30][31][32][33][34] have been performed to analyze the mechanisms of anode erosion, and propose the methods to inhibit the anode erosion. The modeling found that the arc usually attached on the anode surface in the diffusive or constricted forms.…”
Section: Introductionmentioning
confidence: 99%
“…This work introduces a visualization method to analyze plasma-sprayed particles' movement using high-speed video camera footage. In previous works, other authors analyzed flame spray pyrolysis [23], and plasma jet instabilities and fluctuations [24,25], observed using high-speed cameras; the results of a single particle motion are still lacking in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the coatings produced in the plasma spray process are affected by factors such as the plasma torch operation, the state of the generated plasma jet, the properties of the injected powder, and the placement of the substrate [4][5][6][7][8][9][10][11][12][13]. In order to improve the quality and productivity of functional coatings, many studies have been carried out over the past few decades.…”
Section: Introductionmentioning
confidence: 99%